2019
DOI: 10.1029/2019je005938
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Early History of Mercury and Its Core Dynamo by Studying the Crustal Magnetic Field

Abstract: Low‐altitude magnetic field data acquired by MESSENGER (MErcury Surface, Space ENvironment, GEochemistry, and Ranging) over a small portion of Mercury's surface revealed weak crustal magnetic field signatures. Here we study the crustal magnetic anomalies associated with impact craters on Mercury. We assume that the sources of these anomalies consist of impact melt, enriched in impactor iron. We assume that the subsurfaces of Mercury's impact craters have cooled in the presence of a constant global magnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
(86 reference statements)
0
18
0
Order By: Relevance
“…They concluded that this is very unlikely, confirming the results of at the global scale. More recently, Oliveira et al (2019) examined five magnetic field anomalies located above impact craters, and focused on magnetization directions, using a method previously used on the Moon and on Mars (Oliveira and Wieczorek 2017;Thomas et al 2018). This can indeed be used to infer properties about the magnetic field which was present when the magnetization was acquired, when the rock cooled down.…”
Section: Crustal Magnetic Fieldsmentioning
confidence: 99%
“…They concluded that this is very unlikely, confirming the results of at the global scale. More recently, Oliveira et al (2019) examined five magnetic field anomalies located above impact craters, and focused on magnetization directions, using a method previously used on the Moon and on Mars (Oliveira and Wieczorek 2017;Thomas et al 2018). This can indeed be used to infer properties about the magnetic field which was present when the magnetization was acquired, when the rock cooled down.…”
Section: Crustal Magnetic Fieldsmentioning
confidence: 99%
“…How to choose the maximum misfit is an open question. Several authors have chosen a misfit equal to the RMS of the background field, using the assumption that the background field is statistically similar to the unmodeled magnetic field, that is the portion of the magnetization that is not a part of the unidirectionally magnetized anomaly (Oliveira & Wieczorek, 2017; Oliveira et al., 2019; Lee et al., 2019; Thomas et al., 2018). The instrument noise from magnetometers on Lunar Prospector and Kaguya is less than 0.1 nT (Lin et al., 1998; Tsunakawa et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One major concern of magnetic paleopole analyses is the uncertainty associated with the best‐fit magnetization direction. Large uncertainties (near 90° in some cases, e.g., Oliveira et al., 2019; Oliveira & Wieczorek, 2017; Thomas et al., 2018) make it difficult to determine if paleopoles found distant from the present pole truly represent deviation of the dipole axis from the spin axis. Unfortunately, there currently exists no consistent method of describing direction uncertainties across inversion methods (Maxwell et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both spacecraft (Mio and MPO) have nearly symmetric orbits between the northern and southern hemispheres, ideal to separate the magnetic field of internal origin from that of external origin and to perform a spherical harmonic analysis on the planetary internal field. The internal sources include the magnetic field generated by the dynamo mechanism (Wicht and Heyner 2014), the remanent crustal field Oliveira et al 2019), and time-varying induction field in response to changes in the solar wind and magnetospheric conditions (Grosser et al 2004;Johnson et al 2016). The external fields originate in the currents flowing in the magnetosphere, e.g., magnetopause current on the dayside and in the tail, plasma sheet current, field-aligned current, and possibly a partial ring current (Müller et al 2012;.…”
Section: Planetary Fieldmentioning
confidence: 99%